Exploring Farmers' Knowledge and Approaches for Reducing Post-Harvest Physiological Deterioration of Cassava Roots in Malawi - Masamba, Kingsley; Changadeya, W.; Ntawuruhunga, Pheneas; Pankomera, P.; Mbewe, W.; Chipungu, Felistus P. (MDPI, 2022)
Cassava utilisation in Malawi is negatively affected by rapid deterioration of fresh roots, primarily caused by postharvest physiological deterioration (PPD). A study was conducted to assess farmers' knowledge and approaches used to minimize losses from PPD. Multi-stage sampling was used to identify districts, Extension Planning Areas (EPA's) and farmers. Data were collected from 519 farmers using a structured questionnaire. Results revealed that PPD (74.0%) was the major post-harvest constraint followed by pests and diseases (62.1%). Farmers had varying knowledge levels on signs and causes of PPD. They were knowledgeable on PPD signs with 91.5% ably identifying PPD through change of pulp colour. The farmers also had moderate knowledge on causes of PPD, citing high temperature (57.6%) and over-staying of roots (56.2%) as main causes of PPD. Key methods for preventing PPD are: storage (43.0%) and piece-meal harvesting (40.4%). Only 2.6% of the farmers exploited varietal difference in dealing with PPD as some varieties (Sauti, Mpuma, Ching'amba, and Kalasa) take three to five days before showing PPD signs. Farmers' knowledge levels and PPD preventive methods could be strengthened through: provision of training on post-harvest handling, improvement in storage and processing technologies; and application of advanced breeding techniques to exploit genetic variation in cassava germplasm.